تأثير تعليم القواعد لتنمية مهارة القراءة بمدرسة الثانوية الاسلامية الأهلية مفتاح العلوم سورين بجمبر جاوى الشرقية - Muhammad 'Ainul Yaqin; Sihriyatul Jannah (Prodi Pendidikan Bahasa Arab, Universitas Muhammadiyah Tangerang, 2022)
The aim of this research is (1) to find out the effect of teaching grammar to develop reading skill at Al-Ahlia Islamic Secondary School Miftah Al-Ulum, Surin Jember, in the academic year 2020/2021, (2) to know the effect of teaching grammar to develop the skill of oral and silent reading. The research method that the researcher uses is to use the quantitative research method, which is a research that focuses on collecting quantitative data (data in the form of numbers) and uses statistical analysis as a basis for data presentation, data analysis, hypothesis and conclusion: In this study, it is necessary to test the theory that learning the good It has an effect on developing reading skill at Al-Ahlia Islamic Secondary School, Miftah Al-Ulum, Surin, Jember. To collect data, it is the method of questionnaire, observation, interview and documentation. To analyze the data, the researcher uses statistical methods in the form of (Product Moment). And the percentage on the research topic means causal correlation research. After analyzing the data in the form (Product Moment), the following number was obtained: (1) There is an effect of teaching grammar to develop reading skill. The value is 0.959, 1,000 means that